O-136 Once-daily relugolix combination therapy results in sustained reduction in symptoms and improved quality of life in women with uterine fibroids treated over 52 weeks. (6th August 2021) - Lukes, A; Venturella, R; Al-Hendy, A; Nyirady, T; Decleer, W; Petraglia, F; Li, Y; Wagman, R B; Hunsche, E; Stewart, E A
Abstract: Study question: What is the effect of relugolix combination therapy (Relugolix-CT) on symptom burden and health-related quality-of-life (HR-QoL) in patients with uterine fibroids (UF) over 52 weeks? Summary answer: Relugolix-CT demonstrated sustained, clinically meaningful improvement in patient-reported symptom severity and HR-QoL over 52 weeks in women with UF. What is known already: In LIBERTY 1 and 2 randomized clinical trials, once-daily Relugolix-CT (40 mg relugolix, an oral gonadotropin-releasing hormone receptor antagonist, estradiol 1 mg, norethindrone acetate 0.5 mg) significantly reduced menstrual blood loss (MBL) and UF-associated pain versus placebo in women with UF and heavy menstrual bleeding (HMB), and was well tolerated, with bone mineral density (BMD) preservation through 24 weeks. In the LIBERTY long-term extension study, a sustained reduction in MBL was observed along with no new safety signals and BMD maintenance through 52 weeks. Relugolix-CT was previously shown to significantly improve patient-reported symptom severity and HR-QoL through 24 weeks. Study design, size, duration: In the LIBERTY 1 and 2 studies, 770 premenopausal women with ultrasound-documented clinically significant UF and alkaline-hematin documented HMB were randomized 1:1:1 to Relugolix-CT for 24 weeks, relugolix 40 mg for 12 weeks followed by Relugolix-CT for 12 weeks, or placebo for 24 weeks. Women who completed the pivotal studies were eligible to enroll in the 28-week extension study (N = 477 enrolled). Patients included in the extension study received open-label once-daily Relugolix-CT. Participants/materials, setting, methods: Changes from baseline to Weeks 24 and 52 in the Uterine Fibroid Symptom (UFS)-QoL symptom severity scale, Bleeding and Pelvic Discomfort scale (BPD; assessing distress due to HMB, passing blood clots, pelvic pressure/tightness); and HR-QoL (sub)scales were assessed. Higher symptom severity and BPD scores reflect higher severity and distress, respectively; higher HR-QoL scores indicate better outcomes. Least-squares mean changes were provided for the original pivotal-study randomized treatment groups Relugolix-CT and placebo. Main results and the role of chance: A sustained improvement in symptom severity was observed for the Relugolix-CT group from baseline to Weeks 24 and 52, with LS mean changes of –36.9 and –37.3 points, respectively. In patients initially treated with placebo, small changes were observed at Week 24 (–10.8 points), whereas a greater reduction from baseline was demonstrated at Week 52 (–35.0 points) after transitioning to Relugolix-CT. Considering the BPD, measuring distress from key UF symptoms, LS mean changes of –50.9 and –51.3 points were observed in the Relugolix-CT group from baseline to Week 24 and 52, respectively. In patients initially treated with placebo, small changes were observed at Week 24 (–15.9 points), whereas a greater reduction from baseline was demonstrated at Week 52 (–48.6 points) after transitioning to Relugolix-CT. Treatment with Relugolix-CT also resulted in a sustained improvement in different aspects of HR-QoL. LS mean total HR-QoL score increased from baseline to Weeks 24 and 52 by 40.8 and 40.4 points, respectively. In patients initially treated with placebo, small changes were observed at Week 24 (11.4 points), whereas a greater increase from baseline was demonstrated at Week 52 (39.0 points) after transitioning to Relugolix-CT at Week 24. Limitations, reasons for caution: The 28-week LIBERTY long-term extension study was non-comparative. Analyses were performed in a subset of patients who completed the LIBERTY pivotal studies and were eligible for the extension study. However, it is important to note that the demographic and baseline disease characteristics were similar between pivotal and long-term extension populations. Wider implications of the findings: Relugolix-CT resulted in a sustained reduction in UF symptom burden, particularly in terms of distress from key UF symptoms, and a sustained improvement of HR-QoL over 52 weeks. Improvements observed after transitioning from placebo to Relugolix-CT at 24 weeks confirmed the positive effect of Relugolix-CT on UF-associated symptoms and HR-QoL. Trial registration number: NCT03412890